Social Intelligence As A Mean of Empowering Character Education For Students - Santoso, Santoso; Suyahmo, Suyahmo; Rachman, Maman; Utomo, Cahyo Budi (Proceedings of International Conference on Science, Education, and Technology, 2024)
The background of this research is that the behavior of teenagers, including students, lacks concern for good behavior. The character of students tends to be less concerned about the educational environment. This research described social intelligence as the character education empowerment for students. This research uses a qualitative approach with descriptive research type. Several types of methods were used to collect research data, observation, interviews, literature study and documentation for second semester class A students. The results of this research social intelligence is an important aspect to realize character education for the students because education must develop the students' personalities in the real life. Students as the national generation have important roles and responsibilities. Social norms have important roles to realize harmonic social relationships, realizing tranquility, and keeping alert in realizing qualified character students. Social intelligence in students is important to enrich their knowledge and insight. Thus, the students must have sensitivity and awareness of character education empowerment on students.